Recombinant activated protein C attenuates coagulopathy and inflammation when administered early in murine pneumococcal pneumonia - Schouten, Marcel; van 't Veer, Cornelis; Roelofs, Joris J T H; Gerlitz, Bruce; Grinnell, Brian W; Levi, Marcel; van der Poll, Tom (Thrombosis and haemostasis, 2011)
Recombinant human activated protein C (APC), which has both anticoagulant and anti-inflammatory properties, improves survival of patients with severe sepsis. This beneficial effect is especially apparent in patients with pneumococcal pneumonia. Earlier treatment with APC in sepsis has been associated with a better therapeutic response as compared to later treatment. In a mouse model it was recently confirmed that recombinant murine (rm-)APC decreases coagulation activation and improves survival in pneumococcal pneumonia; however, APC did not impact on the inflammatory response. The aim of this study was to determine the effect of APC treatment instigated early in infection on activation of coagulation and inflammation after induction of pneumococcal pneumonia. Mice were infected intranasally with viable S. pneumoniae . Mice were treated with rm-APC (125 μg) or vehicle intraperitoneally 12 hours after infection and were sacrificed after 20 hours, after which blood and organs were harvested for determination of bacterial outgrowth, coagulation activation and inflammatory markers. In this early treatment model, rm-APC treatment inhibited pulmonary and systemic activation of coagulation as reflected by lower levels of thrombin-antithrombin complexes and D-dimer. Moreover, rm-APC reduced the levels of a large number of cytokines and chemokines in the lung. When administered early in pneumococcal pneumonia, rm-APC inhibits systemic and pulmonary activation of coagulation and moreover exerts various anti-inflammatory effects in the lung.